Determinants of foreign direct investment in 31 Asian countries for the 2002 - 2017 period - Thareeq Adhi Chandra; Rossanto Dwi Handoyo (Contemporary Economics, 2020)
This research aims to analyze the determinants of Foreign Direct Investment (FDI) in 31 Asian countries in 2002 - 2017. The determinant variables of FDI are political stability, inflation rate, trade openness, exchange rate, market size and interest rate. This study uses the Generalized Method of Moment (GMM) method or dynamic panel. The study results show that political stability, trade openness, and market size has positive relationship with the FDI inflows of the country. The inflation rate variable has a negative relationship with the entry of FDI in the host country. In comparison, exchange rates and interest rates do not relate to the host country's inflow of FDI. This study contributes to the government by providing several crucial determinants of FDI, as FDI benefits the host country.
Keywords: P45; D25; E22; 330; Foreign direct investment; political stability; inflation rate; market size; trade openness; interest rate; exchange rate